ANALISIS RESEPSI GENERASI Z TERHADAP REPRESENTASI GENERASI SANDWICH DALAM FILM 1 KAKAK 7 PONAKAN - Arya Dhanutirta; Ade Kusuma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines Generation Z's reception of the representation of the sandwich generation in the Indonesian film 1 Kakak 7 Ponakan. Using a qualitative approach and Stuart Hall's encoding/decoding model, data were collected through in-depth interviews with six purposively selected Generation Z informants. The findings reveal three interpretive positions: dominant-hegemonic, negotiated, and oppositional. Informants in the dominant-hegemonic position viewed Moko's sacrifice as a symbol of family responsibility and maturity. Those in the negotiated position accepted family responsibility while emphasizing personal boundaries and mental well-being. In contrast, informants in the oppositional position rejected the film's idealized portrayal of self-sacrifice, arguing that it oversimplifies the realities of the sandwich generation. Overall, the findings show that Generation Z actively negotiates the meanings of family responsibility, sacrifice, and personal well-being. The study highlights film as a space where these meanings are negotiated within contemporary Indonesian families.